Solitary Fibrous Tumors of the Pleura - Örki, Alpay; Eryiğit, Hatice; Akın, Oral; Patlakoğlu, Suat; Koşar, Altuğ; Hacıibrahimoğlu, Gökhan; Arman, Bülent (Fırat University, 2007)
Objectives: The aim of this study is to evaluate the clinical behavior of the solitary fibrous tumors of pleura and the optimal surgical approach for these rare tumors. Material and Methods: We have reviewed the records of six patients who underwent tumor resection in our clinic between 1997 and 2004 retrospectively. Results: Six patients were operated in this period and the mean age was 42.3 years. None of them have been exposed to asbestosis. Symptoms were presented in five patients. All patients underwent thoracotomy. Tumor was originated from visceral pleura in five patients and parietal pleura in one. All patients underwent tumor excision. Mean diameter for tumor was 14cm (range 6 to 24). Pathology results were reported as benign solitary fibrous tumor of the pleura for all the six patients. Resection was complete in all patients. There was no postoperative mortality and major complications. No recurrence has been observed during the mean 53.5 months follow-up. Conclusion: Solitary fibrous tumors of the pleura are rare neoplasms and can reach to giant diameters. Complete surgical resection is the optimal treatment for these tumors and risk of malignancy in larger masses should be remembered. ©2007, Firat University, Medical Faculty

Giriş: Bu çalışmanın amacı plevranın soliter fibröz tümörlerinin klinik davranışını değerlendirerek nadir görülen bu tümörlerin, optimal cerrahi yöntemini belirlemektir. Gereç ve Yöntem: 1997 ve 2004 yılları arasında, kliniğimizde soliter fibröz tümör rezeksiyonu yapılan 6 hastanın kayıtları retrospektif olarak incelendi. Bulgular: Opere edilen altı hastanın yaş ortalaması 42.3 idi. Hiçbir hastada asbest temas öyküsü yoktu. Beş olgu semptomatikti. Tüm olgulara torakotomi yapıldı. Beş hastada tümör viseral plevradan, birinde ise parietal plevradan kaynaklanmaktaydı. Olgularımızda tümör total olarak eksize edildi. Ortalama tümör çapı 14 cm (6-24) idi. Patoloji sonuçları altı olguda da plevranın benign soliter fibröz tümörü olarak raporlandı. Olguların hepsinde komplet rezeksiyon yapıldı. Postoperatif mortalite ve major komplikasyon saptanmadı. Ortalama 53.5 aylık takipte rekürrens gözlenmedi. Sonuç: Plevranın soliter fibröz tümörleri nadir görülen neoplazmalardır ve büyük boyutlara ulaşabilir. Komplet cerrahi rezeksiyon, bu tümörlerin optimal tedavisidir ve büyük kitlelerde malignite akılda tutulmalıdır. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Plevranın Soliter Fibröz Tümörleri